Control of matrix metalloproteinase production in human intestinal fibroblasts by interleukin 21. Issue 12 (8th May 2006) - Monteleone, G; Caruso, R; Fina, D; Peluso, I; Gioia, V; Stolfi, C; Fantini, M C; Caprioli, F; Tersigni, R; Alessandroni, L; MacDonald, T T; Pallone, F
Abstract : Background: T cell-mediated immunity plays a central part in the pathogenesis of tissue damage in inflammatory bowel disease (IBD). The mechanism by which T cells mediate tissue damage during IBD remains unclear, but evidence indicates that T cell-derived cytokines stimulate fibroblasts to synthesise matrix metalloproteinases (MMPs), which then mediate mucosal degradation. We have previously shown that, in IBD, there is high production of interleukin (IL) 21, a T cell-derived cytokine, which enhances Th1 activity. Aim: To investigate whether IL21 controls MMP production by intestinal fibroblasts. Methods: IL21 receptor (IL21R) was evaluated in intestinal fibroblasts by reverse transcriptase-polymerase chain reaction (RT-PCR) and western blotting. Fibroblasts were stimulated with IL21 and MMPs were evaluated by RT-PCR and western blotting. The effect of a neutralising IL21R fusion protein (IL21R/Fc) on the induction of MMPs in fibroblasts stimulated with IBD lamina propria mononuclear cell (LPMC) supernatants was also evaluated. Results: Intestinal fibroblasts constitutively express both IL21R and the common γ chain receptor, which are necessary for IL21-driven signalling. IL21 enhances fibroblast production of MMP-1, MMP-2, MMP-3 and MMP-9, but not tissue inhibitors of MMP-1 and MMP-2. Moreover, IL21 synergises with tumour necrosis factor α to increase synthesis of MMP synthesis. IL21 enhances MMP secretion without affecting gene transcription and protein synthesis. IBD LPMC supernatants stimulate MMP secretion by intestinal fibroblasts, and this effect is partly inhibited by IL21R/Fc. Conclusions: These results suggest that fibroblasts are a potential target of IL21 in the gut and that IL21 controls MMP secretion by fibroblasts.